2014
DOI: 10.1371/journal.pone.0102117
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Acetyltransferase p300 Regulates the Expression of Pluripotency Factors and Odontogenic Differentiation of Human Dental Pulp Cells

Abstract: p300 is a well-known histone acetyltransferase (HAT) and coactivator that plays vital roles in many physiological processes. Despite extensive research on the involvement of p300 in the regulation of transcription in numerous cell lines, the roles of this protein in regulating pluripotency genes and odontogenic differentiation in human dental pulp cells (HDPCs) are poorly understood. To address this issue, we investigated the expression of OCT4, NANOG and SOX2 and the proliferation and odontogenic differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Another report showed that a short pre-application of 5-aza-dC for 24 h increased the responsiveness of DPSCs to osteogenic differentiation protocols [79], a similar result to the one obtained after preconditioning DPSCs for 48 h with BIO or WNT-3A, as we showed in our own previous research [13]. Regarding other epigenetic marks such as acetylation, it was reported that p300, a well-known histone acetyltransferase, also played an important role in maintaining the stemness of DPSCs [80]. Moreover, different types of histone deacetylases or HDACs such as HDAC1, HDAC2, HDAC3, HDAC4, and HDAC9 act as important accelerators of odontoblast differentiation [81][82][83] and a similar effect has been described for histone demethylases like KDM6B, which removes H3K27me3 tags [84].…”
Section: Discussionsupporting
confidence: 86%
“…Another report showed that a short pre-application of 5-aza-dC for 24 h increased the responsiveness of DPSCs to osteogenic differentiation protocols [79], a similar result to the one obtained after preconditioning DPSCs for 48 h with BIO or WNT-3A, as we showed in our own previous research [13]. Regarding other epigenetic marks such as acetylation, it was reported that p300, a well-known histone acetyltransferase, also played an important role in maintaining the stemness of DPSCs [80]. Moreover, different types of histone deacetylases or HDACs such as HDAC1, HDAC2, HDAC3, HDAC4, and HDAC9 act as important accelerators of odontoblast differentiation [81][82][83] and a similar effect has been described for histone demethylases like KDM6B, which removes H3K27me3 tags [84].…”
Section: Discussionsupporting
confidence: 86%
“…Increasing evidence revealed that deregulation of miRNAs is associated with initiation and progression of many diseases such as cancer, stroke, cardiovascular diseases, depression, and regenerative diseases (Gholamin et al, ; Hoseini et al, ; Jafari et al, ; Keshavarzi et al, ; Khanmohammadi et al, ; Mirzaei et al, ; Mirzaei, ; Moridikia et al, ; Mirzaei et al, ; Mirzaei et al, ; Rabieian et al, ; Tavakolizadeh et al, ). MiRNAs could be involved in the regulation of several genes related to dental stem cells fate (Wang et al, ). Hence, identification of them could help to better understand the underlying mechanisms involved in dental stem cell fate.…”
Section: Molecular Mechanisms In the Regulation Of Cellular Differentmentioning
confidence: 99%
“…Hence, identification of them could help to better understand the underlying mechanisms involved in dental stem cell fate. Several studies revealed that miRNAs play a key role in activation or inactivation of many genes related to cell differentiation of dental tissue stem cells such as angiogenic differentiation, osteogenic, and odontogenic (Wang et al, ). MiRNAs have different expressions in various cell populations (Fathullahzadeh et al, ; Mohammadi et al, ; Mirzaei et al, ; Mirzaei et al, ; Salarinia et al, ; Saadatpour et al, ).…”
Section: Molecular Mechanisms In the Regulation Of Cellular Differentmentioning
confidence: 99%
“… 25 , 26 , 38 Histone acetylations and deacetylations play crucial roles in regulations of gene expression and may promote pulp repair and regeneration. 25 , 26 , 38 , 39 , 40 Therefore, studies on epigenetic regulations in restorative dentistry have grown in importance.…”
Section: Reviewmentioning
confidence: 99%
“… 13 In addition, histone acetyltransferase and non-coding RNAs may influence odontogenic differentiation. 40 , 42 Epigenetic factors present at each developmental stage can affect the developmental processes. 13 Thus, some studies have proposed that epigenetic events during tooth development may lead to dental differences in monozygotic twins having identical genotypes.…”
Section: Reviewmentioning
confidence: 99%